Ameliorative effect of cotreatment with the methanolic leaf extract of Urtica dioica on acute kidney injury induced by gentamicin in rats - Saeed Hajihashemi; Mahboubeh Ahmadi; Ali Chehrei; Fatemeh Ghanbari (Mashhad University of Medical Sciences, 2020)
Objective: Effects of cotreatment with Urtica dioica (UD) methanolic leaf extract on gentamicin (GM)-induced acute kidney injury were evaluated in rats. Materials and Methods: Male Wistar rats (n=32) were separated into four groups. Gentamicin (100 mg/kg/day, IP) was injected for eight days with or without UD methanolic extract (200 mg/kg/day, gavage). The renal blood flow (RBF) and systolic blood pressure of rats were recorded. Concentration of creatinine, blood urea nitrogen (BUN), sodium, and potassium and osmolarity were measured in the urine and plasma samples. Oxidative stress level was determined by assessment of the levels of antioxidant power (FRAP) and lipid peroxidation (MDA) in the renal tissue. The renal injury and histopathological changes in the kidney were determined by microscopic evaluations. Results: Administration of UD extract along with GM, compared to GM group, significantly decreased the amounts of plasma creatinine and BUN, urinary sodium excretion, fractional excretion of sodium and potassium, and MDA levels but significantly increased creatinine clearance, urine osmolarity, renal blood flow and FRAP levels. Conclusion: The cotreatment of UD extract can attenuate renal injury of GM by reduction of oxidative stress, lipid peroxidation, and oxygen free radicals. The potential nephroprotective effects of UD extract are probably mediated via its antioxidant and anti-inflammatory activity.